2012
DOI: 10.1519/jsc.0b013e3182260455
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Threshold Assessment Through the Ventilatory Method During Roller-Ski Skating Testing: Right or Wrong?

Abstract: This study aimed at questioning the validity of the ventilatory method to determine the anaerobic threshold (respiratory compensation point [RCP]) during an incremental roller-ski skating test to exhaustion. Nine elite crosscountry skiers were evaluated. The skiers carried out an incremental roller-ski test on a treadmill with the V2 skating technique. Ventilatory parameters were continuously collected breath by breath, thanks to a portable gas exchange measurement system. Poling signal was obtained using inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 22 publications
4
8
0
Order By: Relevance
“…With regards to the relationships between breathing and poling frequencies, all five tests had a tendency to show an increased BF-PF coupling with increased workload and a higher PF than BF during the initial workloads. This is in line with the previous literature [ 18 ]. With regards to the five specific tests, three kinds of BF-PF relationships were observed: 1) In the DP test, BF and PF were synchronised (1:1 BF to PF ratio) almost from the very beginning; 2) the V1 and DS tests showed statistical differences in early and late stages as the BF trend surpassed the PF trend in a cross-like pattern; and 3) the NW and V2 tests presented substantially different BF and PF values except in the last two stages.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…With regards to the relationships between breathing and poling frequencies, all five tests had a tendency to show an increased BF-PF coupling with increased workload and a higher PF than BF during the initial workloads. This is in line with the previous literature [ 18 ]. With regards to the five specific tests, three kinds of BF-PF relationships were observed: 1) In the DP test, BF and PF were synchronised (1:1 BF to PF ratio) almost from the very beginning; 2) the V1 and DS tests showed statistical differences in early and late stages as the BF trend surpassed the PF trend in a cross-like pattern; and 3) the NW and V2 tests presented substantially different BF and PF values except in the last two stages.…”
Section: Discussionsupporting
confidence: 94%
“…Despite the determination of both VT 1 and VT 2 being challenging because the plots did not always clearly show two inflection points, all VTs except the VT 1 of one subject's DP test were determined. These difficulties were expected as a result of a previous V2 study [ 18 ] which concluded that the determination of VT 2 from Ventilatory gas analysis must be used cautiously in exercises involving upper body movements. It was explained that the PF entrains the BF, preventing the usual inflection-like behaviour of the Ventilatory variables.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both of which may also have an influence on anaerobic threshold and potentially VO2 max. From a practical point of view, the findings from those studies allow us to establish that, when a really tight coordination exists between breathing and locomotor rhythms, the determination of the anaerobic threshold, thanks to the ventilatory method, must be used cautiously because it mainly depends on mechanical factors (Faber, 2012).…”
Section: Discussionmentioning
confidence: 99%